2022
DOI: 10.1108/hff-01-2022-0039
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the lattice Boltzmann method and the finite difference technique of thermal convection in closed domains with heaters

Abstract: Purpose The purpose of this paper is to investigate numerically thermal convection heat transfer in closed square and cubical cavities with local energy sources of various geometric shapes. Design/methodology/approach The analyzed regions are square and cubical cavities with two isothermally cold opposite vertical walls, whereas other walls are adiabatic. A local energy element of rectangular, trapezoidal or triangular shape is placed on the lower surface of the cabinet. The lattice Boltzmann technique has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Their study showed that the thermal boundary conditions applied to the cavity walls and the cylinder placement direction have significant effects on the total melting time of their studied material. Gibanov et al 22 presented comparative studies of the lattice Boltzmann procedure and the finite difference approach of thermal convection heat transfer in square and cubic cavities in the presence of local energy sources of different geometrical forms. In addition to using the pure LBM method to simulate this type of thermal problem, investigations carried out in the literature have shown that the coupling of this technique with the finite difference method (FDM) can offer many advantages in terms of computational efficiency and accuracy 23–27 .…”
Section: Introductionmentioning
confidence: 99%
“…Their study showed that the thermal boundary conditions applied to the cavity walls and the cylinder placement direction have significant effects on the total melting time of their studied material. Gibanov et al 22 presented comparative studies of the lattice Boltzmann procedure and the finite difference approach of thermal convection heat transfer in square and cubic cavities in the presence of local energy sources of different geometrical forms. In addition to using the pure LBM method to simulate this type of thermal problem, investigations carried out in the literature have shown that the coupling of this technique with the finite difference method (FDM) can offer many advantages in terms of computational efficiency and accuracy 23–27 .…”
Section: Introductionmentioning
confidence: 99%